Liberalising the energy markets of Western Europe: A computable equilibrium model approach - Finn Roar Aune; Rolf Golombek; Sverre A. C. Kittelsen; Knut Einar Rosendahl (University of Oslo, Department of Economics, 2001)
Using a computable equilibrium model, we examine the short-run effects of a radical liberalisation of the West European natural gas and electricity markets. In each model country, oil, gas, coal and electricity are produced, traded and consumed. There are world markets for oil and coal, and well-integrated competitive markets for gas and electricity in Western Europe. Gas and electricity are transported and traded across markets under the assumption of ideal third-party access regimes for transportation and limited capacities in the transportation networks. We find that relative to the base year 1996, a radical liberalisation reduces the average end-user price of natural gas by around 20 per cent, and the average end-user price of electricity by around 50 per cent. Supply of electricity increases by around 20 per cent, mainly due to increased coal power production. After such liberalisation, coal power emerges with the largest market share of electricity production in Western Europe.
Keywords: 330; Energiemarkt; Erdgas; Elektrizität; Deregulierung; Allgemeines Gleichgewicht; Westeuropa